Covariate analysis of tusamitamab ravtansine, a DM4 anti‐CEACAM5 antibody‐drug conjugate, based on first‐in‐human study. (22nd February 2022) - Pouzin, Clemence; Tod, Michel; Chadjaa, Mustapha; Fagniez, Nathalie; Nguyen, Laurent
Abstract: Tusamitamab ravtansine is an anti‐CEACAM5 antibody‐drug conjugate indicated in patients with solid tumors. Based on a previous developed semimechanistic model describing simultaneously pharmacokinetic (PK) of SAR408701, two of its active metabolites: DM4 and methyl‐DM4 and naked antibody, with integration of drug‐to‐antibody data, the main objective of the present analysis was to evaluate covariate's impact in patients from phase I/II study ( n  = 254). Demographic and pathophysiologic baseline covariates were explored to explain interindividual variability on each entity PK parameter. Model parameters were estimated with good precision. Five covariates were included in the final PK model: body surface area (BSA), tumor burden, albumin, circulating target, and gender. Comparison of BSA‐adjusted dosing and flat dosing supported the current BSA‐based dosing regimen, to limit under and over exposure in patients with extreme BSA. Overall, this model characterized accurately the PKs of all entities and highlighted sources of PK variability. By integrating mechanistic considerations, this model aimed to improve understanding of the SAR408701 complex disposition while supporting key steps of clinical development.